(3OQGSGJ LOjOI aj EYLGR GdbQBf (B:s (3efGgL JWHjbjI aj JhXja GddZI (B/s - (3GdeWYfj, YHO GdYXje EHQGgje eMeOs 1931-2008 ((3GdbGgQI (B:s (3ecJHI hgHI ,s, 2014)
(3jJfGhd GdcJGH (B((3OQGSGJ LOjOg aj EYLGR GdbQBf(B) (3hGdPj bGe HJCdjaI YHO GdYXje EHQgje eMeO GdeWYfj hjJfGhd GdehVhYGJ GdCJjI gPg OQGSI LOjOI aj GdEYLGR GddZhj GdHdGZj ddbQBf hgi LOjOI deG ajgG ef OQGSGJ eJYdbI HGdEYLGR aj GdbQBf efP HOC GdHMK ai gPG GdeLGd MJi GdGf hGdJj jZdH YdjgG GdJYeje hJQcf ddbdjd ef GdJeKjd hGdThGgO ceG jZdH YdjgG hUa GdEYLGR ef GdNGQL s
Keywords: (3bQBfs -- (3eHGMK YGeIs -- (3GdEYLGR GddZhjs